2009
DOI: 10.1029/2008jb005899
|View full text |Cite
|
Sign up to set email alerts
|

Moho depth and Vp/Vs ratio in peninsular Italy from teleseismic receiver functions

Abstract: [1] We present a new data set of Moho depth estimates for peninsular Italy, obtained from receiver functions analysis and a grid search approach. Teleseismic records from 174 broadband seismic stations were used to compute the receiver function data set. In general, our results agree well with previous knowledge, adding original information in many regions where previous data were lacking or uncertain. We find broad regions with consistent Moho depth, namely, (1) the peri-Tyrrhenian areas bordering the homonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
124
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 56 publications
21
124
0
Order By: Relevance
“…& The accuracy of the seismic velocity structure determined using teleseismic receiver functions is a complex problem since it strongly depends on many factors. Usually many tens or hundreds good-quality seismograms of teleseismic events are recorded by a single permanent broadband station (e.g., Piana Agostinetti and Amato 2009;Geissler et al 2008). However, even a large number of seismograms do not guarantee a good azimuthal coverage (e.g., Radjaee et al 2010).…”
Section: Discussion Of the Deviations Uncertainties And Errorsmentioning
confidence: 99%
“…& The accuracy of the seismic velocity structure determined using teleseismic receiver functions is a complex problem since it strongly depends on many factors. Usually many tens or hundreds good-quality seismograms of teleseismic events are recorded by a single permanent broadband station (e.g., Piana Agostinetti and Amato 2009;Geissler et al 2008). However, even a large number of seismograms do not guarantee a good azimuthal coverage (e.g., Radjaee et al 2010).…”
Section: Discussion Of the Deviations Uncertainties And Errorsmentioning
confidence: 99%
“…The ZK technique has been applied worldwide in multiple studies (e.g., FRANÇA and ASSUMPÇ AO 2004;GEISSLER et al 2008;PIANA AGOSTINETTI and AMATO 2009;LLOYD et al 2010;GALLACHER and BASTOW 2012) and is a well-established method to estimate depths and V p /V s ratios for simple crustal structures. Complex tectonic environments prove to be a challenge for ZK technique, since the RF time series are composed of a multitude of converted phases due to the occurrence of several seismic discontinuities in the crust (e.g., CHAMPION et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…From the Ionian Sea and below Calabria to the Tyrrhenian Sea, a narrow and deep subducting oceanic slab, possibly confined by tears Faccenna et al, 2004;Rosenbaum et al, 2008), is imaged by all studies Spakman, 1992, 2000;Amato et al, 1993;Spakman et al, 1993;Morelli, 1997, 2003;Di Stefano et al, 1999;Lucente et al, 1999;Faccenna et al, 2003Faccenna et al, , 2004Chiarabba et al, 2008;Lucente and Margheriti, 2008;Panza and Raykova, 2008;Piana Agostinetti and Amato, 2009;Scafidi et al, 2009). The Calabrian slab flattens and merges with the Apenninic slab under the Tyrrhenian Sea at the upper-mid mantle transition zone (Spakman et al, 1993;Morelli, 1997, 2003;Lucente et al, 1999;Faccenna et al, 2003Faccenna et al, , 2004.…”
Section: Seismic Tomographymentioning
confidence: 95%
“…Below the Central-Southern Apennines, at shallower levels, most authors recognize a wide gap within the subducting lithosphere Spakman, 1992, 2000;Amato et al, 1993;Spakman et al, 1993;Morelli, 1997, 2003;Di Stefano et al, 1999;Lucente et al, 1999;Spakman and Wortel, 2004;Piana Agostinetti and Amato, 2009), identified as slab detachment by Spakman et al (1993) and Piana Agostinetti and Amato (2009). To explain this geometry, Wortel and Spakman (2000) invoked a process of lateral migration of the slab detachment, while other authors proposed either cessation of the subduction (Di Stefano et al, 1999) or presence of slab tears (Faccenna et al, 2004;Di Stefano et al, 1999;Chiarabba et al, 2008;Rosenbaum et al, 2008) due to the heterogeneous Adriatic-Ionian lithosphere.…”
Section: Seismic Tomographymentioning
confidence: 97%